1999
DOI: 10.1007/s004220050580
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ON and OFF pathways for visual contrast measurement

Abstract: Abstract. We propose a novel model of visual contrast measurement based on segregated ON and OFF pathways. Two driving forces have shaped our investigation: (1) establishing a mechanism selective for sharp local transitions in the luminance distribution; (2) generating a robust scheme of oriented contrast detection. Our starting point was the architecture of early stages in the mammalian visual system. We show that the circuit behaves as a soft AND-gate and analyze the scale-space selectivity properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Also, Nirenberg and Meister (1997) have shown that transient and motion-sensitive responses in ganglion cells may be produced by self-inhibitory feedback of the amacrine cells in mouse retina (for similar results, see Berry, Brivanlou, Jordan, & Meister, 1999;Victor, 1987;Crevier & Meister, 1998). Computational models also suggested that self-inhibition may exist in cells sensitive to light-dark contrast (Neumann, Pessoa, & Hanse, 1999). Disinhibition can effectively reduce the amount of inhibition where there is a large area of bright input, and self-inhibitioncan give rise to oscillations in the response over time.…”
Section: Introductionmentioning
confidence: 87%
“…Also, Nirenberg and Meister (1997) have shown that transient and motion-sensitive responses in ganglion cells may be produced by self-inhibitory feedback of the amacrine cells in mouse retina (for similar results, see Berry, Brivanlou, Jordan, & Meister, 1999;Victor, 1987;Crevier & Meister, 1998). Computational models also suggested that self-inhibition may exist in cells sensitive to light-dark contrast (Neumann, Pessoa, & Hanse, 1999). Disinhibition can effectively reduce the amount of inhibition where there is a large area of bright input, and self-inhibitioncan give rise to oscillations in the response over time.…”
Section: Introductionmentioning
confidence: 87%
“…The neural architecture shown in Fig. 3b is sharing some similarities with the one presented in 55 to measure contrast. However, they are both fundamentally different as one is focusing on measuring spatial contrast with no consideration to the temporal domain, while the other detects the maximum contrast in time and in space, by detecting the shortest duration between polarity changes.
Figure 3Spiking neural network.
…”
Section: Methodsmentioning
confidence: 99%
“…This is motivated from data and models for retinal ganglion cells (Koenderink & van Doorn, 1990;Rodieck, 1965). In these models, field components were integrated either linearly (Marr & Hildreth, 1980;Rodieck, 1965) or with other mechanisms (Furman, 1965;Grossberg, 1970), all of which can be combined into one formal framework (Neumann, Pessoa, & Hanse, 1999).…”
Section: Bottom-up Construction With Biologically Plausible Representationsmentioning
confidence: 99%